Vector order determines protection against pathogenic simian immunodeficiency virus infection in a triple component vaccine by balancing CD4+and CD8+T-cell responses - Sauermann, Ulrike; Radaelli, Antonia; Stolte-Leeb, Nicole; Raue, Katharina; Bissa, Massimiliano; Zanotto, Carlo; Krawczak, Michael; Tenbusch, Matthias; Überla, Klaus; Keele, Brandon F.; Morghen, Carlo De Giuli; Sopper, Sieghart; et al. (Journal of Virology, 2017)
An effective AIDS vaccine should elicit strong humoral and cellular immune responses while maintaining low levels of CD4+T cell activation to avoid the generation of target cells for viral infection. The present study investigated two prime-boost regimens, both starting vaccination with single cycle immunodeficiency virus, followed by two mucosal boosts either with recombinant adenovirus (rAd) or fowlpox virus (rFWPV) expressing SIVmac239 or SIVmac251gag/polandenvgenes, respectively. Finally, vectors were switched and systemically administered to the reciprocal group of animals. Only mucosal rFWPV immunizations followed by systemic rAd boost significantly protected animals against a repeated low-dose, intrarectal challenge with pathogenic SIVmac251 resulting in a vaccine efficacy (i.e. risk reduction per exposure) of 68%. Delayed viral acquisition was associated with higher levels of activated CD8+T cells and Gag-specific IFN-γ secreting CD8+cells, low virus-specific CD4+T cell responses and low Env antibody titers. In contrast, the systemic rFWPV boost induced strong virus-specific CD4+T cell activity. rAd and rFWPV also induced differential patterns of the innate immune responses, thereby possibly shaping the specific immunity. PlasmaCXCL10levels after final immunization correlated directly with virus-specific CD4+T cell responses and inversely with the number of exposures to infection. Also, the percentage of activated CD69+CD8+T cells correlated with the number of exposures to infection. Differential stimulation of the immune response likely provided the basis for the diverging levels of protection afforded by this vaccine regimen.IMPORTANCEA failed phase II AIDS vaccine trial led to the hypothesis that CD4+T cell activation can abrogate any potentially protective effects delivered by vaccination or promote acquisition of the virus because CD4+T helper cells, required for an effective immune response, also represent the target cells for viral infection. We compared two vaccination protocols that elicited similar levels of Gag-specific immune responses in rhesus macaques. Only the animal group that had a low level of virus-specific CD4+T cells in combination with high levels of activated CD8+T cells was significantly protected from infection. Notably, protection was achieved despite the lack of appreciable Env-antibody titers. Moreover, we show that both, the vector and the route of immunization affected the level of CD4+T cell responses. Thus, mucosal immunization with FWPV-based vaccines should be considered as potent prime in prime-boost vaccination protocols.
EVALuna2:33748